Exploiting the Microbiota for the Diagnosis of Anal Precancerous Lesions in Men Who Have Sex With Men. (5th February 2021) - Ron, Raquel; Cabello, Alfonso; Gosalbes, María José; Sánchez-Conde, Matilde; Talavera-Rodríguez, Alba; Zamora, Javier; Monge-Maillo, Begoña; Jiménez, Daniel; Martínez-Sanz, Javier; López, Yolanda; Crespillo, Clara; Velasco, Tamara; et al.
Abstract: Background: While the microbiota has been associated with human papillomavirus malignant transformation, it is unclear whether anal bacteria could improve the low specificity of anal cytology for the screening of high-grade intraepithelial squamous neoplasia (HSIL) Methods: We recruited men who have sex with men undergoing anal cytology and high-resolution anoscopy. We assessed the microbiota composition from fecal samples and cytobrush anal samples using 16S ribosomal DNA sequencing in participants with or without biopsy-proven HSIL (bHSIL). We selected bacterial biomarkers based on their linear discriminant analysis. We assessed their predictive performance using logistic regression and bootstrap resampling. Results: We included 128 individuals, 47 (36.7%) with bHSIL and 99 (77.3%) with human immunodeficiency virus. We detected 40 potential predictors of bHSIL. Ruminococcaceae NK4A214 group, Alloprevotella genus, Prevotella melanonigenica, and Ruminococcaceae UCG-014 were the most predictive of bHSIL. From 35 false-positive cytologic results, the combination of these 4 biomarkers with the anal cytology reclassified to true-negative 33 individuals (94%) and showed good diagnostic performance (area under the receiver operating characteristic curve, 0.805; 95% confidence interval, .728–.882). Conclusions: We found anal-associated bacteria indicative of a higher risk of precancerous anal lesions, which combination was highly specific. The microbiota could be developed as a complementary diagnostic tool to overcome the limitations of the current screening strategy for anal cancer. Abstract : We here propose a set of bacterial biomarkers indicative of a higher risk of precancerous anal lesions, which combination was highly specific. Our findings indicate that the microbiota could be developed as a complementary diagnostic tool for anal cancer screening.